End of life : nursing solutions for death with dignity - Keegan, Lynn.; Drick, Carole Ann.; Watson Caring Science Institute (New York : Springer, 2011)
This professional clinical guide presents nursing administrators and nurses in acute care agencies, nursing homes, hospice, and palliative care settings with detailed implementation strategies for accommodating dying persons and their loved ones as they make the transition from physical life. Written by nurses for nurses, the text promotes compassionate end-of-life care and provides a roadmap to changing the death experience of patients and their families into one that is peaceful, personal, and dignified. It presents theoretical frameworks for end-of-life care, the need for and the development of the Golden Room concept and how it fits into these frameworks.
Foundations. Why people die -- Death with dignity -- A place for death with dignity: "The Golden Room" -- End-of-life issues -- End-of-life costs of care -- Legal and ethical barriers -- Theory and Practice. Theoretical frameworks -- Letting go: the body's shutdown process -- Changing the consciousness around death and dying -- Spiritual perspectives -- Palliative care to hospice to "The Golden Room" -- Implementation Steps. Guide to implementing "The Golden Room" concept with health professionals -- Creating a plan or proposal -- Preparing for the future.
"Watson Caring Science Institute."
Includes bibliographical references and index.
Keywords: Hospice nurses; Terminal care